Weber's thesis "the spirit of capitalism"as a starting point for finding spiritual potentials in business and management environment. - Kučera, Dušan; Nový, Ivan, 1956-; Riedlbauch, Václav, 1947-2017; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
Submitted work is based on a critical evaluation of Weber's thesis "the spirit of capitalism", which justified by the "Protestant ethic". The author uses the Weber's starting point for the processing of general spiritual concept, which has a major impact on the emergence, development and maintenance of the economic environment, business and management. After clarification of the fundamental concepts, the work focuses on clarifications to the phenomenon of spirituality, which is connected with the entrepreneurial and managerial activities. Presence of the spiritual character of business potentials was divided into positive and negative factors. General spiritual factors are reflected on the background of basic religious systems -- Judaism, Christianity (Protestantism, Roman Catholicism and Eastern Orthodoxy), Islam, Hinduism, Buddhism and other Asian directions. Spiritual perspectives are compared with the concepts of the science that have their limits or potentials. The practical part is devoted to the proof of spiritual influences on business and economic development. The work culminates in a research of spiritual factors and potentials of entrepreneurship and management between the selected entrepreneurs and managers. The collected factors and potentials are summarized and proposed for their use in the entrepreneurial and managerial practice or managerial training.
Vedoucí práce: Ivan Nový
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations